Effect of the addition of residue of the clarification of vegetable oil in the mechanical behavior of a lateritic tropical soil - Araujo, Weliton Eduardo Lima; Almeida, Danilo Guimarães; Ribeiro, Rênystton de Lima; Mendonça, Layson Barbosa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The objective of this work was to evaluate the performance of the mechanical resistance of the discarded clay and residual lateritic tropical soil mixture in order to provide an environmentally adequate destination for the residue through its application in base layers and sub-base of flexible pavements. The mixtures were composed of 100% solids, 100% discarded clarifying clay (DCC), 05% DCC + 95% solids, 10% DCC + 90% solids, 20% DCC + 80% 70% soil and 40% DCC + 60% soil, totalizing seven experimental units. To evaluate the mechanical performance, the Proctor and California Support Index (CBR) compaction tests were carried out at intermediate and modified energies. The mixtures obtained similar granulometric behavior to the local soil, observing a change of the fine fraction due to the increase of the same residue. The results of mechanical resistance indicated a better performance of the mixtures with 10% of DCC + 90% soil and 20% of DCC + 80% soil, in the modified energy, being recommended as material for the execution of pavements. For the other mixtures, it is recommended only the use in the execution of sub-bases of flexible pavements.